Sorcery, rights, and cosmopolitics among the Tau-Buhid Mangyan in Mts. Iglit-Baco National Park - Rosales, Christian A. (2019)
The refusal of the Tau-Buhid to be intruded upon by the Philippine Government in their ancestral domain is intensfying. The State is unaware that resistance among the inhabitants in the remote regions of Mindoro is grounded in their practice of an offensive magic called "amurit". Although this term appears recurrently in mediatory discussions, it is dismissed by government agents who view it as an excuse to avoid compliance with State law, and for lack of 'scientific validation'.

For the Tau-Buhid, amurit is a complex and harmful magic that is effective only when the practitioner is truly the offended party. Being 'offended' in this context includes betrayal of trust, insult, or cheating, as well as transgression of consensus based on customary law. It gives the aggrieved the right to retribution and to compensation, including by death. In this paper, it is held that the rights-making dynamics of amurit should be viewed as integral to the Tau-Buhid notion of sociality. Moreover, the Tau-Buhid assert and insist on a collective 'right to isolation' in order to protect the potency of their magic. The essay is a necessary reflection on the State's concept of governance vis-a-vis the Indigenous Peoples' assertion of the right to isolation in the context of the Mts. Iglit-Baco National Park. It argues for acknoledgement of cosmopolitical entologies within the discourse of conservation science.